1992
DOI: 10.1212/wnl.42.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia and probable senile dementia of the Alzheimer type in the Framingham Study

Abstract: We determined the prevalence of dementia and probable senile dementia of the Alzheimer type (SDAT) for biennial Exam 17 of the Framingham cohort (1982/1983). The prevalence of dementia was 30.5/1,000 for men and 48.2/1,000 for women and increased with advancing age. Cases of probable SDAT constituted 55.6% of all dementia cases. THe prevalence of SDAT was 11.7/1,000 for men and 30.1/1,000 for women and also increased with advancing age. Prevalence of dementia and probable SDAT were greater for women than men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
251
5
10

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(290 citation statements)
references
References 0 publications
16
251
5
10
Order By: Relevance
“…The prevalence of AD found in our casuistry differs from the ones found in other hospital series from our region; it is lower than the ones found by Godoy et al (1998) and by Nitrini (1993), which are similar to numbers found in population studies 11,22 and is higher than the one found by Silva (2001). Concerning vascular dementia, the prevalence found in our study is close to the one found by Silva (2001), being higher than Nitrini's (1993) and lower than Godoy et al (1998).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The prevalence of AD found in our casuistry differs from the ones found in other hospital series from our region; it is lower than the ones found by Godoy et al (1998) and by Nitrini (1993), which are similar to numbers found in population studies 11,22 and is higher than the one found by Silva (2001). Concerning vascular dementia, the prevalence found in our study is close to the one found by Silva (2001), being higher than Nitrini's (1993) and lower than Godoy et al (1998).…”
Section: Discussioncontrasting
confidence: 59%
“…Male sex was predominant as observed in Silva's study (2001), but not in Godoy et al ' (1998). Population studies usually point out higher prevalence of female sex for dementias in general and for Alzheimer's disease 11,22,23 , even though some of them do not demonstrate such difference 24,25 . Concerning the vascular dementia, some studies have shown a higher prevalence of the male sex 26 and others have shown no difference 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that as many as 30-50% of women over the age of 85 have a dementia or AD (Bachman et al 1992) and 30-40% of people with AD have depressive and/or psychotic symptoms (Wragg and Jeste 1989), investigating the role of progestogens in the related symptomology of these conditions is of interest. An approach taken to investigate the role of P 4 and its metabolites was a double transgenic mouse model of familial AD that express a human presenilin 1 Δ exon 9 deletion mutation, which corresponds to a form of early-onset AD, and overexpression of a chimeric mouse/human amyloid precursor protein (APPswe; Borchelt et al 1996aBorchelt et al , 1996bBorchelt et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The defining features of AD include progressive, global cognitive impairment that develops in individuals whose brains manifest densities of senile plaques that exceed those expected for age. 4,5 However, patients with this disorder manifest remarkable inter-individual variability in other clinical characteristics, including age at symptomatic onset; rate and pattern of pro-gression; emergence of disturbances of mood, thought, perception, and behavior; development of extrapyramidal symptoms; and presence of a family history of ADlike dementia.…”
Section: Introductionmentioning
confidence: 99%